Decision synthesis in engineering design of technological attachment - D. P. Kunkevich; I. L. Kovaleva; A. A. Baryshau (Системный анализ и прикладная информатика, 2021)
Synthesis of the engineering design decisions is considered. The fixtures for locating and clamping parts to be tooled at the manufacturing operations are the design objects. An approach to topology and parametric design are proposed. Most efficiently these tasks are solved at the function level. Finally, geometry models and design drawings are needed for manufacturing. Fixture action is to mate bases of fixture object with function faces of fixture locators. This is constraining the degrees of freedom of object. Every base constrains certain degree of freedom. In accordance with quantity and quality of that degrees, certain locators are appointed to the base and them must be positioned resulting in the a locating chart. The quality of the locating chart may be evaluated by the several criteria, for example, by it dimensions. Unsatisfactory solution may be followed by redistributing degrees of freedom among the bases or editing positions of locators within the bases. Thus the design is decomposed onto two independent tasks of different levels.